The Effect of Locomotor Games on Gross Motor Ability of Elementary School Students - Indah Verawati; Rahma Dewi; Bessy Sitorus Pane; Nurkadri Nurkadri (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to examine the effect of locomotor games on gross motor skills of elementary school students. The design of this study used a quantitative pre-experimental design type one-group pretest-posttest. The sample in this study amounted to 20 people with. purposive sampling technique The instrument used in this study used the TGMD-2 Test of Gross Motor Development-2. The research methodology used in this study was data analysis using paired t-test statistical techniques. In the paired t-test analysis, the pretest and posttest p value = 0.000 (p <0.05). From these results it can be concluded that there is a significant positive effect of locomotor games on the gross motor of elementary school students.